ANALISIS SELF- CONCEPT SISWA SMA DALAM PEMBELAJARAN MATEMATIKA MELALUI MODEL PROBLEM BASED LEARNING - PUTRI , CANTIKA MAHARANI; HASANUDDIN (LPPM Universitas Banda Naira, 2025)
This study explores students' self-concept in mathematics learning using the Problem Based Learning model. The research method used is descriptive qualitative. Data were obtained through interviews with teachers and students filling out questionnaires. The results of the analysis showed that the implementation of Problem Based Learning had a positive impact on students' self-concept. Students showed a higher interest in mathematics, actively asked questions, and felt close to the material. Although there were still students with negative views, Problem Based Learning brought positive changes in students' understanding and views of mathematics. The analysis of students' self-concept involved dimensions of knowledge, expectations, and assessments. Students rated their mathematics abilities at a moderate level, but still had a desire to achieve a higher ideal self-image. Although there was a decrease in views on the relationship between abilities possessed and ideal abilities, the overall self-concept score was still in the moderate category. The results of this study indicate that Problem Based Learning can be an effective tool in shaping students' self-concept towards mathematics.